Multiomics Analysis of Molecules Associated with Cancer in Mesenchymal-Stem-Cell-(MSC)-Derived Exosome-Treated Hepatocellular Carcinoma Cells - Wen-Yong Gao; Chantana Boonyarat; Nutjakorn Samar; Benjabhorn Sethabouppha; Pornthip Waiwut (Current Issues in Molecular Biology, 2024)
Hepatocellular carcinoma (HCC) is the most common form of liver cancer in humans, with an increasing incidence worldwide. The current study aimed to explore the molecular mechanisms that inhibit the proliferation of HepG2 cells, a hepatoblastoma-derived cell line. MSC-derived exosomes (UC-MSCs) were prepared with a median particle size (N50) of 135.8 nm. Concentrations of UC-MSCs ranging from 10 μg/mL to 1000 μg/mL were applied to HepG2 cell cultures and compared to untreated and anticancer drug-treated HepG2 cells. A combined approach was employed, integrating a proteomic analysis of UC-MSCs, metabolomic analysis of HepG2 cells, and transcriptomic profiling of HepG2 cells to decipher the inhibitory mechanisms of UC-MSC exosomes on HepG2 cell growth. Treatment with a high concentration of UC-MSCs led to a notable reduction in HepG2 cell viability, with survival decreasing by 65%. A proteomic analysis of UC-MSCs revealed enriched degranulation processes in Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, in addition to the known exosomal pathways. Transcriptomic profiling showed distinct changes in the expression of genes related to hepatocellular diseases in UC-MSC-treated HepG2 cells, contrasting with changes observed in HepG2 cells treated with the chemotherapeutic agent doxorubicin (DOX). Combined with a metabolomic analysis, the detailed GO and KEGG pathway analyses indicated that pathways associated with neutrophil extracellular trap formation played a critical role in mediating protein degradation and suppressing central carbon metabolism in cancer cells. Our results revealed that the UC-MSC treatment mimicked molecular mechanisms similar to those involved in neutrophil extracellular trap formation, exhibiting effects on HepG2 cell growth suppression that differed from those of chemical cancer drugs. Notably, the UC-MSC treatment demonstrated that protein degradation in HepG2 cells was regulated through canonical signaling pathways activated by bacterial peptides in neutrophils. This research has provided valuable insights into the potential of MSC-derived exosomes as a therapeutic approach for cancer treatment in the future.